27 NEUROPSYCHIATRIC SYSTEMIC LUPUS ERYTHEMATOSUS: THE 25-YEAR MAYO CLINIC EXPERIENCE. (1st March 2005) - Murali, N. S.; Auethavekiat, P.; Moder, K. G.; Manek, N. J.
Abstract : Introduction: The diverse spectrum of focal or diffuse, central and peripheral nervous system involvement in neuropsychiatric systemic lupus erythematosus (NPSLE), its inconsistent relationship with overall disease activity as it continues to remain a leading cause of morbidity and mortality in SLE makes its diagnosis extremely challenging. In 1999, the American College of Rheumatology (ACR) proposed criteria that include 19 case definitions for NPSLE. Purpose: We reviewed all patients with the diagnosis of NPSLE at the Mayo Clinic, over a 25-year period to better understand the pattern of presentation of NPSLE and prevalence with frequency distribution of every criterion as defined by the ACR. Methods: We retrospectively reviewed 117 patients with presumed NPSLE presenting at the Mayo Clinic, Rochester, from 1976 to 2001. Twenty-seven records that failed to meet ACR diagnostic criteria or did not have a confirmed nervous system involvement were excluded. Abstracted data included general demographics, clinical presentation, duration of SLE, blood tests, imaging studies, electroencephalography (EEG) and mortality. Summary of Results: Majority were women (n = 77), Caucasian (88.9%) with a mean age of 37.6 years (range: 11 to 70 yrs) at presentation. Twenty-six developed NPSLE prior to demonstrable SLE symptoms and 12 developed it concurrently. Twenty-four of them died with a median survival of 168 months. Seizure was the most common presentation (38.9%), followed by cerebrovascular accidents and cognitive impairment (31.1%). Interestingly, we identified 3 patients who presented with features of parkinsonism as demonstrated by cogwheel rigidity, bradykinesia, dysphonia, and gait disturbance. Conclusion: We believe that this study is among the largest population sample in the United States of this rare but devastating illness. Review of literature reveals that most studies performed so far involve small sample populations and are predominantly case reports. Central nervous system involvement was much more frequent than peripheral nervous system. We unearth a hitherto undescribed and novel presentation of NPSLE and suggest that it be added to the current ACR case definitions.